Hypertension Accelerates Alzheimer’s Disease-Related Pathologies in Pigs and 3xTg Mice - Shih, Yao-Hsiang; Wu, Shih-Ying; Yu, Megan; Huang, Sheng-Huai; Lee, Chu-Wan; Jiang, Meei-Jyh; Lin, Pao-Yen; Yang, Ting-Ting; Kuo, Yu-Min (Frontiers in Aging Neuroscience, 2018)
Epidemiological studies suggest there is an association between midlife hypertension and increased risk of late-life Alzheimer’s disease (AD). However, whether hypertension accelerates the onset of AD or is a distinct disease that becomes more prevalent with age (comorbidity) remains unclear. This study aimed to test the possible relationship between hypertension and AD pathogenesis. Two animal models were used in this study. For the first model, 7-month-old Lanyu-miniature-pigs were given the abdominal aortic constriction operation to induce hypertension and their AD-related pathologies were assessed at 1, 2 and 3 months after the operation. The results showed that hypertension was detected since 1 month after the operation in the pigs. Levels of Aβ, amyloid precursor protein, RAGE, phosphorylated tau and activated GSK3β in the hippocampi increased at 3 months after the operation. For the second model, 3xTg mice at the ages of 2, 5 and 7 months were subjected to the “two-kidney-one-clip” operation to induce hypertension. One month after the operation, blood pressure was significantly increased in the 3xTg mice in any age. Aβ, amyloid plaque load, and phosphorylated tau levels increased in the operated mice. Furthermore, the operation also induced shrinkage in the dendritic arbor of hippocampal dentate gyrus granule neurons, leakage in the blood-brain barrier, activation in microglia, and impairment in the hippocampus-dependent learning and memory in the 3xTg mice. In conclusion, hypertension accelerates the onset of AD. Blood pressure control during midlife may delay the onset of AD.